Is It Still Safe to Visit Artificial Attraction in Jakarta? - Felix Goenadhi (FIRM Journal of Management Studies, 2022)
This study aims to determine the Importance and Performance of CHSE (Cleanliness, Health, Safety, and Environment Sustainability) protocol and Customer Satisfaction Index at Man-Made or Artificial Attraction during the new normal. The circular contains health protocols that must be applied by every entrepreneur and/or manager, employee, and tourist. CHSE (Cleanliness, Health, Safety, and Environment Sustainability) is one of the health protocols based on cleanliness, health (health), security (security), and environmental sustainability implemented by the government for the prevention and control of the Coronavirus. Disease (COVID-19) in every related facility, the community environment, to tourism destinations. This study is a quantitative study using primary data collected through an online questionnaire. This study uses a probability sampling technique with a sample size of 331. This study was conducted with validity and reliability tests and descriptive analysis using Importance and Performance Analysis (IPA) techniques and performed calculations to get the Customer Satisfaction Index (CSI). The results show that the importance of performance analysis correlate to the Customer Satisfaction Index (CSI) was 72.56%. Researchers feel the lack of research on CHSE (Cleanliness, Health, Safety, and Environment Sustainability) in Man-Made Attraction and the lack of scientific literature on CHSE (Cleanliness, Health, Safety, and Environment Sustainability) with the theme of industrial vehicles.